BLOCKCHAIN TECHNOLOGY FOR ERP SYSTEMS: A REVIEW - Arjun Reddy Kunduru (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Enterprise resource planning (ERP) platforms integrate critical business operations, including manufacturing, inventory, accounting, human resources, and supply chain management, into unified systems for automation and analytics. However, traditional centralized ERP architectures have notable limitations around security, transparency, costs, and process integrity. ERP data silos inhibit trust, provenance tracking, and collaboration across organizational boundaries. Recently, blockchain distributed ledger technology has emerged as a promising approach to transforming ERP by enabling decentralized verifiable workflows, immutable record keeping, and end-to-end transaction traceability. Blockchain offers a paradigm shift for ERP by distributing control across a peer-to-peer network organized around consensus, cryptography, and innovative algorithms. Early research and prototypes demonstrate blockchain’s potential to enhance security, trust, provenance, automation, and standardization in enterprise systems. Blockchain ERP pilots show feasibility in supply chain tracking, accounting, procurement, manufacturing, and more. By sharing tamper-evident ledgers across companies, blockchain builds transparency, integrity, and collaboration into ERP workflows. Several technical concepts underpin blockchain ERP capabilities. Distributed ledgers cryptographically chain transaction records. Consensus protocols like proof-of-work and Byzantine fault tolerance enable unanimous agreement on valid state changes across nodes. Smart contracts automate multi-step workflows based on predefined conditions. Hashing, public-key encryption, and zero-knowledge proofs provide security and privacy. Together, these constructs allow decentralized and verifiable ERP processes. However, challenges remain prior to enterprise adoption at scale. Blockchain ERP must still overcome hurdles integrating with legacy systems, coordinating complex cross-organizational ecosystems, scaling transaction throughput and data storage, and reducing implementation costs. Data privacy also requires consideration under public blockchain models. In conclusion, blockchain shows immense yet nascent promise for revolutionizing outdated ERP platforms once integration, coordination, scaling, and cost obstacles are surmounted through further research and development. By transforming how enterprises architect and optimize mission-critical systems, blockchain may profoundly disrupt enterprise computing and business processes. The technology remains in its early stages but holds revolutionary potential for ERP and inter-organizational collaboration.